Removal of ammonium ions by capacitive deionization and membrane capacitive deionization units - Sakar, Hacer; Karataş, Okan; Canbolat, Cigdem Balcik; Keskinler, Bulent; Karagunduz, Ahmet (Desalination Publ, 2017)
In this study, capacitive deionization (CDI) and membrane capacitive deionization (MCDI) unit cells were used to remove NH4+ ions. The influences of operating parameters such as the applied voltage, the initial ammonium concentration and the flow rate on the effectiveness of ammonium removals were investigated. In addition, the effects of different membrane types on MCDI performances were also studied. The results showed that, the electrosorption performances of CDI and MCDI increased by increasing the initial concentration, flow rate and the applied potential. It was observed that the adsorption capacity of MCDI unit was much higher than that of CDI due to the presence of ion-exchange membranes. MCDI technology may provide better advantages on ammonium removal.
Membrane Science and Technology Conference of Visegrad Countries (PERMEA) / Membrane and Electromembrane Processes Conference (MELPRO) -- MAY 15-19, 2016 -- Prague, CZECH REPUBLIC
Keywords: Capacitive deionization; Electrosorption; Ammonium removal